Two new associations for the halophytic vegetation of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Data about the syntaxonomy of plant communities with significant presence of two locally rare in Ukraine halophilous species Frankenia pulverulenta L. and Camphorosma annua Pall. are presented. Communities with Frankenia pulverulenta in Ukraine were discovered by authors for the first time in Northern Black Sea Region (Skadovsk district of Kherson oblast) and in Kerch Azov Sea Region (Lenine district of the Crimea). Based on the cluster analysis of these communities in Juice software using Modified TWINSPAN algorithm these relevés were identified as new syntaxon Puccinelio fominii-Frankenietum pulverulentae Davydova & Davydov ass. nova. The latter belongs to the new for Ukraine high rank syntaxa – the alliance Frankenion pulverulentae Rivas-Martínez ex Castroviejo & Porta 1976, the order Frankenietalia pulverulentae Rivas-Martínez ex Castroviejo & Porta 1976 and the class Saginetea maritimae Westhoff & al. 1962. All these syntaxa of ephemeric halo-subnitrophilous vegetation on saline badlands were known from Atlantic and Western Meditterranean only. Frankenia pulverulenta was previously treatened in Ukraine as attendant species in communities of other halophilous vegetation classes (Therosalicornietea Tüxen in Tüxen & Oberdorfer 1958, Kalidetea foliati Mirkin & al. ex Rukhlenko 2012 and Festuco-Puccinellietea Soó ex Vicherek 1973). Results of the comparative analysis of the vegetation dominated by Camphorosma annua are available too. These communities formed two clusters which are treated as two different syntaxa based on their features of specific composition and environmental peculiarities. The first syntaxon is known in Ukraine as Camphorosmo annuae-Puccinellietum distantis Shelyag-Sosonko & Solomakha 1987 but it is quite similar to Camphorosmetum annuae Soó 1934 distributed in Central Europe. The latter name has priority by the date of publication so it is to be used for Ukrainian communities. The second syntaxon was described as new association Puccinellio giganteae-Camphorosmetum annuae Davydov ass. nova. Both associations with Camphorosma annua belongs to the order Puccinellietalia Soó 1947 from the class Festuco-Puccinellietea but two different alliances: Puccinellion limosae Soó 1934 (Camphorosmetum annuae) and Puccinellion giganteae Golub & Solomakha ex Dubyna & Neuhäuslová 2000 (Puccinellio giganteae-Camphorosmetum annuae). Nomenclatural citations, types and diagnostic species have been presented for all syntaxa.
Keywords: Frankenia pulverulenta and Camphorosma annua communities, syntaxonomy, Saginetea maritimae, Festuco-Puccinellietea.